Solving the Equation: (a+1)(a+2) = 0
This equation represents a simple quadratic equation in factored form. To find the solutions for 'a', we can utilize the Zero Product Property. This property states that if the product of two or more factors is zero, then at least one of the factors must be zero.
Applying the Zero Product Property

Set each factor equal to zero:
 (a + 1) = 0
 (a + 2) = 0

Solve for 'a' in each equation:
 a + 1 = 0 => a = 1
 a + 2 = 0 => a = 2
Solutions
Therefore, the solutions to the equation (a + 1)(a + 2) = 0 are:
a = 1 and a = 2
These values of 'a' make the original equation true.